Prevention in practice – a summary. Issue 1 (December 2015) - Birch, Stephen; Bridgman, Colette; Brocklehurst, Paul; Ellwood, Roger; Gomez, Juliana; Helgeson, Michael; Ismail, Amid; Macey, Richard; Mariotti, Angelo; Twetman, Svante; Preshaw, Philip; Pretty, Iain; et al.
Abstract Background This paper is a summary document of the Prevention in Practice Conference and Special Supplement of BMC Oral Health. It represents the consensus view of the presenters and captures the questions, comments and suggestions of the assembled audience. Methods Using the prepared manuscripts for the conference, collected materials from scribes during the conference and additional resources collated in advance of the meeting, authors agreed on the summary document. Results The Prevention in Practice conference aimed to collate information about which diseases could be prevented in practice, how diseases could be identified early enough to facilitate prevention, what evidence based therapies and treatments were available and how, given the collective evidence, could these be introduced in general dental practice within different reimbursement models. Conclusions While examples of best practice were provided from both social care and insurance models it was clear that further work was required on both provider and payer side to ensure that evidence based prevention was both implemented properly but also reimbursed sufficiently. It is clear that savings can be made but these must not be overstated and that the use of effective skill mix would be key to realizing efficiencies. The evidence base for prevention of caries and periodontal disease has been available for many years, as have the tools and techniques to detect, diagnose and stage the diseases appropriately. Dentistry finds itself in a enviable position with respect to its ability to prevent, arrest and reverse much of the burden of disease, however, it is clear that the infrastructure within primary care must be changed, and practitioners and their teams appropriately supported to deliver this paradigm shift from a surgical to a medical model.